The Implementation of the Core Tax Administration System (CTAS) as an Effort to Increase Tax Revenue - Ahmad Rofiudin; Fajar Ramadhan; Mariam Mariam; Siti Chizatun Fitriyah; Nofryanti Nofryanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the implementation of the Coretax Administration System (CTAS) as an effort to increase tax revenue in Indonesian in 2025. The method used in this research uses a literature study method. In this research, the authors explored various literature such as research result, government reports, news articles and documentation related to the development and implementation of Coretax on state revenue. The results of this study show that the implementation of the Core Tax Administration System (CTAS) has proven to be a strategic and effective step in efforts to increase tax revenues in Indonesia. The research results show progress in overall tax revenue performance up to September 2025 when compared to the previous period in 2024.